The celebrants : a novel [large type] - Rowley, Steven, 1971- (Thorndike Press, a part of Gale, a Cengage Company, 2023)
"It's been five years since Jordan Vargas last saw his college friends. Now Jordan, Jordy, Naomi, Craig, and Marielle find themselves at the brink of a new decade, no closer to having their lives figured out. Over the years they've reunited in Big Sur to honor a decades-old pact to throw each other living "funerals," celebrations to remind themselves that life is worth living--and living well. But this reunion is different. They're not gathered as they were to bolster Marielle as her marriage crumbled, to lift Naomi after her parents died, or to intervene when Craig pleaded guilty to art fraud. This time, Jordan is sitting on a secret that will upend their pact"--